Pemberdayaan KWT Citra Mandiri melalui Pengembangan Produk Olahan Berbasis Aloe vera di Kecamatan Tapos, Depok - . Rahmawati; Mohammad Sabariman; Susilo Utomo (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Service activities such as science, technology and the arts for the people (IbM) to the group of women farmers and processors of aloe plant (Aloe vera) namely Citra Mandiri in Tapos Districts, Depok (as a partner) has the following objectives: 1) Standardization of nata Aloe vera product to be a good processed with consistently and desired products; 2) Diversification of Aloe vera products; and 3) Improvement and business management technical training. Community service team, who act as facilitators have been mentoring to improve the product quality Aloe vera nata to be consistent, to develop new products as diversification of candy and puddings of Aloe vera with the appropriate technology for home industries with a current good Manufacturing Practice and hygienic environment. To expand the market access, the team also trained collaborators about food packaging and labeling. In addition, a collaborators become a member of the Creative Industries Association of Depok to increase their market access and network.